A New Approach to Investigation of the Relationship of VLF Signals by Using Longitudinal Analysis Models - Guzel, E.; Yasar, M.; Kilic, M. B.; Canyilmaz, M. (Hindawi Ltd, 2013)
Longitudinal analysis models are applied to analyze very low frequency (VLF) electromagnetic waves signals. They are useful in realization of nuance of relationship between parameters of concern which change over time. VLF data are so important for the communication and determining the disturbances in the lower ionosphere. In this study, we used a four-day VLF signal data which come from transmitter stations located at two different countries to Elazi. g receiver system. A very important feature of this data is that there is a strong relationship between days and signals. At first, the exploratory data analysis was applied for identification of data. Then, marginal, random-effects, and transitional models were used to analyze the data, respectively. The marginal model is found more appropriate than the other models used for VLF data analyses. As a result of this process, a new method has been added to the analysis of VLF signal data.